Students’ Views on the Use of Google Translate in English Language Learning - Yolifi, Fuva Wersa; Afrianto , Afrianto; Masyhur, Masyhur (PROJECT (Professional Journal of English Education), 2025)
This study explores students’ views on the use of Google translate in English Language Learning, focusing on students’ perception on the use of Google translate and how them see it. The primary issue identified is that many students rely on Google Translate when encountering difficulties with vocabulary and long texts. Compared to other translation applications, Google Translate is widely favored among students because it offers a helpful features.  The research employs a mixed-method approach, combining questionnaires and semi-structured interviews for data collection. The population of this research is third-year English students, Faculty of Teacher Tranining and Education at the University of Riau using random cluster sampling, 38 students were selected from 118 population.. The analyzing data using descriptive statistical and qualitative analysis by Miles and Huberman (1994). The findings reveal that students generally hold positive views on using Google Translate with an average total score 66.77 in which score classification  is  57-95. The participants have positive views about Google Translate, which is the application is very helpful in learning English, for completing assignments and language development.